Investigating injector angles to eliminate spray-wall impingement in a manifold port injection system of gasoline engines - Nguyen, Uy; Nguyen, Phu; Duong, Cuong; Phung, Duoc; Nguyen, Quan; Pham Xuan, Assoc.Prof.Dr Phuong (Journal of Military Science and Technology, 2023)
There has been an outstanding improvement in injection technology in the spark ignition (SI) engines’ fuel supply systems, from traditional carburettors with throttle body injection (TBI), manifold port or multi-point injection (MPI) to direct injection (DI). This paper has developed an MPI intake manifold model and investigated fuel injector angles using a multiphase CFD package provided by FloEFD software. A wide range of injector angles from 22 to 30 degrees has been investigated in order to evaluate the influence of the injector angle on the wall-wetting issue, a critical problem of manifold injection systems in SI engines. The intake air pressure differential in the manifold was also evaluated. The results show that the fuel injector angle affects the multiphase flow in the MPI system. The manifold diameter meets the design specifications, and the pressure differential in the manifold is quite small. With an injector angle of 25 degrees, the wall-wetting issue is minimal. This model could be used for further studies on engine performance and emission formation.